The Impact of SPAC Mergers on Financial Performance and Growth: Evidence from the Italian Market - Domenico Piatti (European Scientific Journal, ESJ, 2024)
This study examines the impact of SPAC mergers on the financial performance of Italian firms, focusing on profitability (ROE, ROI), revenue growth, and workforce expansion. A Propensity Score Matching (PSM) combined with a Difference-in-Differences (DiD) approach is employed, analyzing Business Combinations completed between 2015 and 2019, with data spanning from 2013 to 2022 (two years pre- and three years post-merger). Results indicate a decline in profitability post-merger, consistent with challenges like overvaluation and integration difficulties, while sales growth improved significantly. The findings highlight the importance of strategic planning and regulatory oversight in optimizing SPAC mergers, addressing a critical gap in the Italian market where research is limited. This analysis provides valuable insights for managers and policymakers navigating the evolving SPAC landscape in Italy.